Risk Prediction of Postoperative Complications in Lower Gastrointestinal Perforation Based on Preoperative Serum Cholinesterase Levels - Masahisa Ohkuma; Yasuhiro Takano; Keisuke Goto; Atsuko Okamoto; Muneyuki Koyama; Tadashi Abe; Takafumi Nakano; Yasuhiro Takeda; Makoto Kosuge; Ken Eto (Journal of the Anus, Rectum and Colon)
Objectives: Cholinesterase is recognized as a marker for nutritional status and associated with inflammatory conditions. The present study aims to evaluate the association between cholinesterase and postoperative complications in patients with lower gastrointestinal perforation. Methods: The study included 71 patients who had undergone emergency surgery for lower gastrointestinal perforation. We retrospectively investigated the relationship between preoperative serum cholinesterase levels and postoperative complications. Complications were defined as Clavien-Dindo (C-D) grade II or higher, with severe complications classified as C-D grade III-V. We performed univariate and multivariate analyses to evaluate independent risk factors for postoperative complications. Results: Among of all, 43 patients (61%) developed postoperative all complications (C-D II), and 17 patients (24%) developed severe complications (C-D III-V). In multivariate analysis, cholinesterase (p=0.006), C-reactive protein (p=0.028), and blood loss (p=0.028) were independent risk factors for postoperative all complications (C-D II). Also, cholinesterase (p=0.006) was an independent risk factors for postoperative severe complication (C-D III- V). Patients in the cholinesterase-low group had significantly lower preoperative hemoglobin (p=0.001), albumin (p<0.001), and prognostic nutritional index (p<0.001), as well as higher C-reactive protein (p=0.010), neutrophil-lymphocyte ratio (p=0.038), proportion of wound infection (30% vs. 4.8%, p=0.026) and abdominal abscess (30% vs. 0.0%, p=0.003) compared to those in the cholinesterase-high group. Conclusions: Preoperative serum cholinesterase levels may be associated with postoperative severe course in patients with lower gastrointestinal perforation. This association underscores the potential role of cholinesterase as an indicator of nutritional and inflammatory status.